Malaria reportage in Punch and Nigerian Tribune Newspapers (2013)
The study examined the reportage of malaria from January to December, 2011 in Punch and Nigerian Tribune newspapers. It identified the frequencies of malaria reports in these two newspapers according to the story category, the prominence given to the stories, the sources of story and themes including causes, effect, prevention and treatment of malaria. The simple random system sampling technique was employed to select the two newspapers and content analysis method was adopted to examine them. Results showed that the malaria reportage rates in the reviewed newspapers were 5.9% in 269 Punch newspapers and 7.1% in 308 Nigerian Tribune newspapers. No definite pattern of variation was observed in malaria reportage rate in the two newspapers. However, the highest malaria reports were observed in Punch in December and in April in Nigerian Tribune. Malaria reports were more of news stories in Punch (62.5%) and in the Nigerian Tribune (59.1%) respectively. None of the two newspapers placed malaria report under editorial column. There was no malaria cartoon and advert in Punch and Nigerian Tribune respectively. The two newspapers placed most of their malaria reports in the less important category with percentage rate of 81.3% and 77.3% in Punch and Nigerian Tribune respectively. In‐house was the most frequent source of malaria reports with frequencies of 43.8% in Punch and 54.5% in Nigerian Tribune. Reports on malaria prevention had the highest frequency of 62.5% in Punch and 45.5% in Nigerian Tribune. The study concludes that malaria reports were not given enough coverage in the two newspapers studied. It, therefore, suggests that malaria reportage rates be increased in Nigerian newspapers so as to create more awareness to the public on malaria issues.